Dalga Boyu Bölmeli Çoğullama Kullanan Optik Hatlarda Fiber Bragg Izgaraların Performansa Etkisinin İncelenmesi - BÖCEKÇİ, VEYSEL GÖKHAN (My University, 2018)
Dalga boyu bölmeli Çoğullama (WDM) sistemi, kanal kapasitesini artırarak yüksek hızlı veri iletimi sağlayabilen bir fiber optik teknolojidir.Bu teknoloji ile, tek bir kablo üzerinden farklı dalga boylarında birden fazla kanal üzerinden veri iletimi sağlanabilir. Bu çalışmada,dalga boyu bölmeli çoğullama tekniği ve optik ağların sundukları üstünlükler birleştiğinde haberleşme sisteminde oluşacak veri kalitesi artışıve veri kayıplarının önüne geçmek için Fiber Bragg Izgaraların (FBG) kullanımının performans artırmadaki etkisi incelenmiştir. ÇalışmalarOptisystem programının 15 sürümü kullanılarak gerçekleştirilmiştir. Simüle edilen sistemlerde, hat uzunluğu 10,100 ve 200 kmşeklinde seçilmiş ve veri hızı olarak ise 10,40 ve 80 Gbps değerleri kullanılmıştır. FBG uzunluk referans aralığı 2 mm ila 8 mm alınmıştır.Ölçüm sonuçlarına göre, FBG kullanılması, kullanılmamasına kıyasla Bit Hata Oranı (BER) değerini yaklaşık %50 oranında azaltıp,Q-faktörü değerini yaklaşık %6 oranında arttırarak hat kalitesine olumlu yönde etki ettiği görülmüştür. Hat kalitesindeki değişimler göz diyagramlarıile birlikte görsel olarak paylaşılmıştır.

The Wavelength Division Multiplexing (WDM) system is a fiber optic technology that can provide high-speed data transmission by increasing channel capacity. With this technology, data can be transmitted over a single cable over multiple channels in different wave lengths. In WDM, the information carrying capacity can be further increased by increasing the data rates per channel or the number of multiplexed channels. This is accomplished by decreasing the channel spacing to 0.2 nm and increasing the number of channels, and is described by the term dense wavelength division multiplexing (DWDM).FBG is obtained by periodically changing the refractive index in a small region of the optical fiber.The basic principle of the sensors based on FBG is to determine the variation of the reflected Bragg wavelength shift due to temperature or stress. In this study, we analyzed the effect of using Fiber Bragg Grating (FBG) gratings to improve the data quality and the loss of data in the communication system when the wavelength division multiplexing technique and the advantages of the optical networks combine. Studies were conducted using version 15 of the Optisystem program. In the simulated systems, the line lengths are taken as 10,100 and 200 km and the data rates are 10,40 and 80 Gbps. The FBG length reference range is 2 mm to 8 mm. According to the measurement results, the use of FBG decreased the Bit Error Rate (BER) value by about 50% and increased the Q-factor value by about 6% compared to the non-using FBG. Changes in line quality are visually shared with eye diagrams. The contribution of the FBG sensor to fiber technology has been investigated in different ways. With these investigations, it is seen that it is possible to increase the quality of data transfer rate by using FBG sensor. WDM and FBG technologies are highly open technologies to further increase data transmission speed. In today’s technology, development studies are carried out to increase the data transmission rate to a higher level. Thanks to these studies, the need for increased data traffic will be reached.
Analyzing of the Effect of Fiber Bragg Gratings on Optical Lines Using Wavelength Division Multiplexing
Keywords: Fizik, Uygulamalı; Mühendislik, Elektrik ve Elektronik